Zinc finger protein ZFP36L1 inhibits influenza A virus through translational repression by targeting HA, M and NS RNA transcripts - Lin, Ren-Jye (Nucleic Acids Res, 2020)
ZFP36L1, a CCCH-type zinc finger protein, is an RNA-binding protein that participates in controlling cellular mRNA abundance and turnover by posttranscriptional regulation. Here, we demonstrated that ZFP36L1 has an important role in host defense against influenza A virus (IAV) infection. Overexpression of ZFP36L1 reduced IAV replication via translational repression of HA, M and NS RNA segment transcripts. IAV infection upregulated cellular ZFP36L1 expression, and endogenous ZFP36L1 knockdown significantly enhanced IAV replication. ZFP36L1 directly binds to IAV NS1 mRNA in the cytoplasm and blocks the expression and function of NS1 protein. Mutation of CCCH-type zinc finger domains of ZFP36L1 lost its antiviral potential and NS1 mRNA binding. Thus, ZFP36L1 can act as a host innate defense by targeting HA, M and NS mRNA transcripts to suppress viral protein translation.